STUDY OF THE DIGITAL ECONOMY DEVELOPMENT: REGIONAL ASPECT - M. Yu. Teplyakova; M. D. Khabib (Вестник университета)
The development of society at the present stage is characterized by the practical implementation of digital technologies in many areas of life. The purpose of this study is to analyze the information support of the development of the digital economy in the regions of the Russian Federation. The methodological approaches of international and national organizations in the system for assessing the development of the country's informatization have been disclosed in the article. A system of indicators of the national system for monitoring the development of the digital economy, which reflects the development factors of the information society and the use of information and communication technologies, has been presented. A comparative assessment of the composition and content of international and national indicators for assessing the development of the information society has been given. The calculation on the components of the information and communication technologies Development Index for each subject of the Russian Federation and the Federal districts has been made, as well as the analysis of variations in this Development Index for the constituent entities of the Russian Federation for 2014–2018 has been carried out.